Revitalizing endangered languages: a digital gamification approach to introduce and sustain Tenyidie culture - Liu, Ruiqian (Nanyang Technological University, 2023)
Indigenous languages are an essential part of the world's cultural diversity, but many of these languages are endangered due to a lack of effective preservation efforts. In Nagaland, India, the Tenyidie language is one such example, with only a few thousand speakers left. To introduce this language to the global audience and sustain its use among younger generations, we propose a digital gamification approach that combines storytelling, game design, and language learning.